THE EFFECT OF PROBLEM-BASED LEARNING (PBL) ON STUDENTS’ WRITING OF EXPOSITION TEXT BY THE TENTH GRADE STUDENTS OF SMKN 2 KURIPAN - Lola Febrianti; Muhammad Muhlisin; Sugianto (Journal of English Education and Literature, 2025)
This study investigates the effect of Problem-Based Learning (PBL) in improving the writing skills of tenth-grade students at SMKN 2 Kuripan, specifically in composing exposition texts. Using a pre-experimental one group pretest and posttest design, the research involved 31 students from class X DPIB 1 in the 2022/2023 academic year. Writing tests, administered as pretest and posttest, served as the primary data collection instruments. The results, analyzed using descriptive and inferential statistics, including a paired sample t-test, showed a significant improvement in students’ writing skills. The mean score increased from 59.65 in the pretest to 74.35 in the posttest, with notable enhancements in content, organization, language use/grammar, and mechanics. The hypothesis test confirmed the effect of PBL, as evidence by a p-value < 0.05, indicating its significant impact on students’ ability to produce well-structured and coherent exposition texts. This study concluded that PBL not only improves students’ critical thinking and collaboration but also enhances motivation and engagement in learning. The null hypothesis was rejected, affirming that PBL positively influences students’ writing skills.